A Case Report on the Clinical Efficacy of Kankayana Vati and Pilovos Ointment, A Novel Topical Agent, in the Management of Second-Degree Hemorrhoids - A. Ashi; S. Sreelakshmi; V. Remya; K. Priyanka; K. K. Bindu; K. Nayana; M. Deepthy; Indu Chandra Bose; G. R. Asish; B. Sheela Karalam (International Journal of Ayurveda and Pharma Research, 2023)
Haemorrhoids, caused by the inflammation and symptomatic enlargement of anal cushions, are a common pathological condition. The conventional medical treatment of haemorrhoids shares similarities with Arsoroga in Ayurveda, both in terms of etiology and clinical features. Kankayana Vati is a widely used internal medicine for haemorrhoids, although the dosage has not been explicitly specified. Additionally, a novel ointment, Pilovos, has been developed for local application to provide symptomatic relief. This case study explores the combined efficacy of Kankayana Vati (2 grams per day) and Pilovos ointment in the management of second-degree haemorrhoids in a 32-year-old male patient.